Alterations in patient plasma microRNA expression profiles following resection of metastatic melanoma. Issue 3 (21st August 2018) - Latchana, Nicholas; DiVincenzo, Mallory J.; Regan, Kelly; Abrams, Zachary; Zhang, Xiaoli; Jacob, Naduparambil K.; Gru, Alejandro A.; Fadda, Paolo; Markowitz, Joseph; Howard, J. Harrison; Carson, William E.
Abstract : Background and Objectives: MicroRNAs (miRs) are noncoding RNAs that regulate protein translation and melanoma progression. Changes in plasma miR expression following surgical resection of metastatic melanoma are under‐investigated. We hypothesize differences in miR expression exist following complete surgical resection of metastatic melanoma. Methods: Blood collection pre‐ and post‐surgical resection was performed in six individuals with solitary melanoma metastases. miR expression in extracted RNA was quantified using the NanoString nCounter Digital Analyzer. Results: Pre‐ and post‐surgical plasma samples contained 216 miRs with expression above baseline. Comparison of postsurgical to preresection samples revealed differential expression of 25 miRs: miR‐let‐7a, miR‐let7g, miR‐15a, miR‐16, miR‐22, miR‐30b, miR‐126, miR‐140, miR‐145, miR‐148a, miR‐150‐5p, miR‐191, miR‐378i, miR‐449c, miR‐494, miR‐513b, miR‐548aa, miR‐571, miR‐587, miR‐891b, miR‐1260a, miR 1268a, miR‐1976, miR‐4268, miR‐4454 ( P  < 0.05). Utilizing P  < 0.0046 as a cutoff to control for one false positive among the 216 miRs revealed that postsurgical melanoma plasma samples had upregulation of miR‐1260a ( P  = 0.0007) and downregulation of miR‐150‐5p ( P  = 0.0026) relative to pre‐surgical samples. Conclusions: Differential expression of miR‐150‐5p and miR‐1260a is present in plasma following surgical resection of metastatic melanoma in this small sample (n = 6) of melanoma patients. Therefore, further investigation of these plasma miRs as noninvasive biomarkers for melanoma is warranted.